Converging coolness and investigating its relation to user experience. Issue 4 (3rd April 2017) - Raptis, Dimitrios; Bruun, Anders; Kjeldskov, Jesper; Skov, Mikael B.
ABSTRACT: Recently a number of studies appeared that operationalised coolness and explored its relation to digital products. Literature suggests that perceived coolness is another factor of user experience, and this adds to an existing explosion of dimensions related to aesthetics, hedonic quality, pragmatic quality, attractiveness, etc. A critical challenge highlighted in prior research is to study the relationships among those factors and so far, no studies have empirically examined the relationship between coolness and other established user experience factors. In this paper, we address this challenge by presenting two studies one that focuses on factors from two cool questionnaires, and one that compares them against existing User eXperience (UX) factors. Our findings show that factors from the two cool questionnaires converge and they also converge to existing, established UX factors. Thus, 11 distinct cool and UX factors converge into 5 for the case of mobile devices. Our findings are important for researchers, as we demonstrate through a validated model that coolness is part of UX research, as well as for practitioners, by developing a questionnaire that can reliably measure both perceived inner and outer coolness as well as the overall coolness judgement based on 5 factors and 21 items.